Pemanfaatan Digital Marketing Melalui Website dan Pelatihan untuk Peningkatan Pemasaran Produk Rumah Panggung di Kelurahan Woloan Kota Tomohon: Pengabdian - Gede Erik Aktama; Marcelitha Tabita Montolalu; Sherly Ernawaty Susanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This Community Partnership Program (PKM) was implemented to enhance the digital marketing capacity of the Woloan Jaya Traditional House Craftsmen Group in Tomohon City, North Sulawesi. The main problem identified was that the marketing activities were still mostly conventional, limiting market reach. This program aimed to support the digital transformation of the business through a participatory approach. The implementation method consisted of: (1) initial situation analysis, (2) development of a product marketing website using the WordPress CMS platform, (3) three training sessions (basic digital marketing, website development and management, marketing management), (4) production of digital promotional content, and (5) ongoing mentoring and monitoring. The results indicate that the website www.woloanjaya.com is active and has begun to be accessed by potential customers. Digital promotional content has been created and utilized as part of the initial campaign, and the partners’ skills in managing social media and website content have improved significantly. The initial impact observed includes increased product visibility online, greater customer interaction through WhatsApp Business, and stronger motivation from partners to utilize digital technology independently. This program is expected to increase sales turnover and expand market reach while contributing to the achievement of university Key Performance Indicators (IKU) through the active involvement of students.